Hideyoshi - Berry, Mary Elizabeth (Harvard University Press, 1989)
Hideyoshi—peasant turned general, military genius, and imperial regent of Japan—is the subject of an immense legendary literature. He is best known for the conquest of Japan's sixteenth–century warlords and the invasion of Korea. He is known, too, as an extravagant showman who rebuilt cities, erected a colossal statue of the Buddha, and entertained thousands of guests at tea parties. But his lasting contribution is as governor whose policies shaped the course of Japanese politics for almost three hundred years.